Sol-Gel Derived Single Layer Zeolite-MgF2 Composite Antireflective Coatings with Improved Mechanical Properties on Polycarbonate - Subasri, R.; Pavithra, S. (Journal of Coating Science and Technology, 2014)
Single layer antireflective coatings with good optical and mechanical properties are difficult to be obtained on temperature sensitive substrates like plastics. This challenge has been taken up in the present study. Single layer MgF2 and for the first time, zeolite 4Å and zeolite 4Å - MgF2 composite antireflective coatings were generated by a wet chemical route on flat polycarbonate sheets and characterized for their reflectance, surface roughness, thickness, porosity, surface morphology and scratch hardness by haze measurement. Autoclaving and boiling water treatment under microwave irradiation were used in case of MgF2 sols and zeolite/zeolite-MgF2 coatings respectively. Pure MgF2 coatings deposited after autoclaving of the MgF2 sol yielded a low refractive index of 1.28 and an average reflectance of 1.9% vis-à-vis 9.7% reflectance for an uncoated polycarbonate substrate over the wavelength range of 400-1100 nm. Single layer zeolite coatings after a brief treatment in boiling water under microwave irradiation yielded a reflectance of 5.1%. A composite zeolite-MgF2 coating exhibited a reflectance of 2.8% and the percentage change in haze after crockmeter testing in case of the composite coating was lower than that of a pure MgF2 coating. This implied that the composite layer had improved mechanical properties combined with good optical properties and could be suitable for practical applications.